UMPSA and MARA strengthen collaboration with a focus on TVET Integration Model Studies - Mimi Rabita, Abd Wahit (UMPSA, 2025)
PEKAN, 18 July 2025 – The recent visit by a delegation from Majlis Amanah Rakyat (MARA), led by its Deputy Director-General (Education), Ir. Dr. Mahzan Teh, to Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) provided a valuable opportunity to strengthen collaboration between the two institutions, particularly in the area of student funding and TVET integration.